Effect of Ageing on Physico-Chemical Properties Of Non-Dairy Ice Cream Mix - Awg Isa, Wan Rosnani (2004)
The rheological characteristics of ice cream mix prepared from palm oil (PO), palm kernel oils (PKO) and their blends with anhydrous milk fat (AMF) at 30:70, 5030 and 70:30 ratios during ageing were studied. The experimental ice cream mixes were compared with a control sample prepared from Ah4F. Ice cream mix containing 33.44% total solids including 10% fat, 11.09% milk solid-non fat (MSNF), 12% sugar, 0.35% commercial blend of emulsifier/stabiliser and water. The rheological properties such as the flow behaviour, Newtonian viscosity (q,) and compliance (J,) were measured after ageing at 4OC for 0, 0.5, 1, 1.5,2 and 24 hr and determined using a controlled stress rheometer (Haake RS 100). The Power Law and Casson equation was employed to estimate the yield stress (z,) of an ice cream mixes. The correlation coefficients (r) for the regression analyses of the square root of the shear stress-shear rate data were represented well by the Casson model (r > 0.99) for all the samples, indicating goodness of fitted. The shapes of the curves of consistency coefficients &) were quite similar for all the experimental samples. The flow behaviour index (n) of the ice cream mixes prepared with palm fi-action (PO and PKO) and their blends were less than 1.0 (range 0.04-0.08) indicating that the mixes were pseudoplastic fluid. The q, at shear rate 20-' indicated that the degree of viscosity in the control sample was higher